2015
DOI: 10.1016/j.bbadis.2015.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin-induced stimulation of the Na+-activated K+ channels is responsible for maintaining the basolateral K+ conductance of the thick ascending limb (TAL) in EAST/SeSAME syndrome

Abstract: The renal phenotype of EAST syndrome, a disease caused by the loss-of-function-mutations of Kcnj10 (Kir4.1), is a reminiscence of Gitelman's syndrome characterized by the defective function in the distal convoluted tubule (DCT). The aim of the present study is to test whether antidiuretic hormone (vasopressin)-induced stimulation of the Na+-activated 80-150 pS K+ channel is responsible for compensating the lost function of Kcnj10 in the thick ascending limb (TAL) of subjects with EAST syndrome. Immunostaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
(54 reference statements)
1
11
0
Order By: Relevance
“…Genetic ablation of KCNJ10 has no effect on the basolateral V m in the TAL due to compensatory upregulation of the 80-pS channel (Zhang et al, 2015), suggesting that depolarization of the basolateral V m in the TAL is unlikely to contribute to salt wasting in KCNJ10 knockout mice and patients with EAST/SeSAME syndrome (Bockenhauer et al, 2009;Scholl et al, 2009). Interestingly, however, the inhibition of the 40-pS channel with Ba 21 reduces the activity of basolateral ClC-Kb Cl 2 channels through mechanisms that are currently unclear but do not appear to involve membrane depolarization (Fan et al, 2015). These data suggest that the natriuretic and diuretic effects of VU0134992 could result, at least in part, in the inhibition of NaCl reabsorption in the TAL, as follows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic ablation of KCNJ10 has no effect on the basolateral V m in the TAL due to compensatory upregulation of the 80-pS channel (Zhang et al, 2015), suggesting that depolarization of the basolateral V m in the TAL is unlikely to contribute to salt wasting in KCNJ10 knockout mice and patients with EAST/SeSAME syndrome (Bockenhauer et al, 2009;Scholl et al, 2009). Interestingly, however, the inhibition of the 40-pS channel with Ba 21 reduces the activity of basolateral ClC-Kb Cl 2 channels through mechanisms that are currently unclear but do not appear to involve membrane depolarization (Fan et al, 2015). These data suggest that the natriuretic and diuretic effects of VU0134992 could result, at least in part, in the inhibition of NaCl reabsorption in the TAL, as follows.…”
Section: Discussionmentioning
confidence: 99%
“…The basolateral K 1 conductance of the cortical TAL is carried by a 40-pS channel that is likely composed of Kir4.1-5.1 heteromeric channels, and an 80-pS channel possibly carried by Na 1 -activated K 1 channels (Fan et al, 2015;Zhang et al, 2015) (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that Kir4.1 function in the cTAL could be compensated is also supported by patch-clamp experiments performed in p9 neonatal Kcnj10 −/− mice demonstrating that the disruption of Kir4.1 stimulates the activity of Na + and Cl − -activated 80- to 150-pS K + channel (K ca 4.1 or slo 2.2) in the cTAL [27;28]. The upregulation of Na-activated 80–150 pS K channel in the TAL may be induced by high vasopressin level in p9 neonatal Kir4.1 knockout mice as evidenced by the finding that AQP2 expression was upregulated [29]. …”
Section: Expression Of Kir41 Along the Nephron Segmentsmentioning
confidence: 99%
“…Moreover, we reasoned that a high vasopressin level may be mainly responsible for the stimulation of ENaC-β and γ expression in p9 neonatal Kcnj10 −/− mice because vasopressin has been shown to stimulate the expression of ENaC-β subunit [63]. Furthermore, our previous studies showed that the disruption of Kir4.1 increased AQP2 expression, suggesting Kcnj10 −/− mice have a high vasopressin level [29]. …”
Section: Expression Of Kir41 Along the Nephron Segmentsmentioning
confidence: 99%
“…Fan et al demonstrated that the vasopressin-dependent stimulation of the 80-150 pS basolateral K + channel in Kcnj10 (Kir 4.1) KO mice counteracts the loss of function of Kir 4.1 in the TAL, preventing defective salt absorption at this nephron site. 86 …”
mentioning
confidence: 99%